Mas Kawin dan Kehormatan Perempuan: Studi Kualitatif Tradisi Meriam Lela pada Masyarakat Kei-Maluku - Hateyong, Elizabeth; Seralarat, Kornelis; Masriat, Cayetanus; Refo, Ignasius Samson S. (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
This research explores the tradition of lela cannon as bride-price in the Kei Islands, focusing on its complex social and cultural relationships. The objective is to comprehend the profound meaning of lela cannon and discuss it within the context of respecting women. A qualitative methodology was utilized, employing the snowball technique for data collection. The study reveals the rich significance of lela cannon and socially and culturally illustrates gender dynamics, where on one hand, women symbolically elevate their social status, and on the other, are degraded to objects of exchange. These findings add a new dimension to the understanding of bridal dowry. The study offers new insights into the social impacts of bridal dowry, including the pressures faced by women and their autonomy.